Analisis dan Implementasi Sistem Informasi Pemasaran dan Penjualan Berbasis Web pada PT. Monabe Medika Mulya - joan; Arijanto, Rudy (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2023)
E-Commerce is a concept that is quite developing in the field of technology. The E-Commerce concept provides many conveniences and advantages when compared to conventional shopping concepts, including all the information that consumers want can be accessed in more detail, quickly without being limited by place and time, and the transaction process can be carried out much more easily. So implementing this system will make it much easier and more profitable for many parties, both consumers and sellers. Development methods in building E-Commerce applications. So Exteme Programming is used to build an E-Commerce application with a case study of the Health Equipment Sales Information System with Business to Customer (B2C) principles at PT Monabe Medika Mulya.